2016
DOI: 10.21315/aamjaf2016.12.s1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Investor Sentiment in Malaysian Stock Market

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…This research extends the works of Tuyon and Ahmad (2014) that provides discussion on the theoretical relations between sentiment and stock market activity and Tuyon et al (2015) that proposed CSI, BSI and FKLI as possible sentiment proxies. The objectives of this paper are to theoretically and empirically examine the heterogeneity roles of these sentiment proxies on aggregate stock market indice returns in the Malaysian setting.…”
Section: "The Market Is Subject To Waves Of Optimistic and Pessimisupporting
confidence: 73%
See 2 more Smart Citations
“…This research extends the works of Tuyon and Ahmad (2014) that provides discussion on the theoretical relations between sentiment and stock market activity and Tuyon et al (2015) that proposed CSI, BSI and FKLI as possible sentiment proxies. The objectives of this paper are to theoretically and empirically examine the heterogeneity roles of these sentiment proxies on aggregate stock market indice returns in the Malaysian setting.…”
Section: "The Market Is Subject To Waves Of Optimistic and Pessimisupporting
confidence: 73%
“…Thirdly, exploration of the possible influence of behavioral risks on asset prices and stock market behavior is warranted as existing studies indicated that the Malaysian stock market is also noted to be less sensitive to changes in fundamental factors and more prone to speculative trading effect (Ariff, Mohamad and Nassir, 1998), and the stock market sometimes portrays an evidence of irrationality and inefficiency (Nassir, 2002). So far, there are no endorsed proxies for investor sentiment in Malaysia, but consumer sentiment index (CSI), business condition servay (BCS) and stock futures index (FKLI) are seen as highly possible proxies for investor sentiment (see Mat Nor, Ibrahim and Rashid, 2013;Tuyon, Ahmad, Matahir;. Selections of these variables are theoretically and empirically derived as non-economic factors that possibly influence investors' thought and indirectly influence stock prices.…”
Section: "The Market Is Subject To Waves Of Optimistic and Pessimimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Berger and Turtle (2012) document that sentiment has greater effect on stocks with specific firm characteristics especially firms that are transparent whereas Zhu and Niu (2016) suggest that firms with high information uncertainties are more affected by sentiment. In a recent study, Tuyon, Ahmad and Matahir (2016) note that degree to which sentiment affects stock prices may differ based on firm size. Accordingly, we include firm-level controls to incorporate this aspect in our analysis.…”
Section: Related Literaturementioning
confidence: 99%
“…Findings showed that there was a difference in the market reaction; either in developed and developing capital markets (Otchere & Chan, 2003;Kadiyala & Rau, 2004;Docking & Koch, 2005;Bagella et al, 2007;Kaniel et al, 2008;Sharma et al, 2008). There are allegations that the difference of the market reaction is not due to the economic aspects, but to some psychological aspects, such as overreaction/ underreaction, overconfidence, loss aversion and framing bias (Tuyon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%